A Note on General Third Geometric-Arithmetic Index of Special Chemical Molecular Structures (Communications in Mathematical Research, 2021)
In theoretical chemistry, the geometric-arithmetic indices were introducedto measure the stability of alkanes and the strain energy of cycloalkanes. In this note,we report the general third geometric-arithmetic index of unilateral polyomino chainand unilateral hexagonal chain. Also, the third geometric-arithmetic index of thesechemical structures are presented.
Keywords: molecular graph; general third geometric-arithmetic index; unilateral polyomino chain; unilateral hexagonal chain.